The production of a national riskscape and its fractures: nuclear power facility location policy in South Korea - Lee, Sang-Hun; Hwang, Jin-Tae; Lee, Jungpil (ERDKUNDE, 2018)
This paper examines the ways in which the Korean developmental state has, until very recently, managed physical risks of nuclear power operations while also pursuing national economic growth. In the literatures on the East Asian developmental states thesis, developmental state deployment of nuclear power as an energy source has been implicitly assumed to be risk-free and insulated from diverse social forces. However, by adopting the concept of the ‘riskscapes’ and examining four nuclear power plant sites (Gori, Uljin, Wolsung and Younggwang), we show how a national riskscape has been designed by the government and has been dynamically contested by diverse actors for various reasons. The nationalized riskscape imposed by the developmental state has landed in each site differently according to the geographical, historical, political, and economic backdrops of the sites. It is within the context of this internally differentiated and contested nuclear power riskscapes that South Korean president Moon Jae-in has vowed to end the use of nuclear power.